Handelsrestriktionen gegen Russland belasten sektoral und regional unterschiedlich stark; Trade restrictions versus Russia will put stress on German sectors and states differently - Mario Jung (Wirtschaftsdienst, 2022)
Die militärische Eskalation in der Ukraine sowie die aufgrund der Sanktionen einsetzenden Bremseffekte für die Kapital- und Handelsströme werden die deutsche Wirtschaft auf makroökonomischer Ebene belasten. In diesem Beitrag soll ein Überblick über die direkten Handelsrisiken gegeben werden: Welche Sektoren und Bundesländer sind besonders durch die starken Belastungen im Warenhandel zwischen Deutschland und Russland betroffen? – – Regarding current trade data, the German economy is not that dependent on their export business with Russia. However regarding imports, risks are clustered due to a high dependence on imports of energy and other raw materials that are not easy to substitute. These risks are also common in all German states. This article also analyses the trade relations of the German states with Russia, presenting the special and unique risks of severe trade disruptions with Russia for the individual German states.
Keywords: F14; O50; 330; Außenhandel; Sanktion; Kriegsfolgen; Deutschland; Russland